GCT-41. RESPONSE-BASED RADIATION THERAPY IN PATIENTS WITH NEWLY DIAGNOSED CENTRAL NERVOUS SYSTEM LOCALIZED GERMINOMA: A CHILDREN'S ONCOLOGY GROUP (COG) PROSPECTIVE PHASE 2 CLINICAL TRIAL. (4th December 2020) - Bartels, Ute; Fangusaro, Jason; Shaw, Dennis; Bhatia, Aashim; Omar-Thomas, Arzu; Wu, Shengjie; MacDonald, Shannon; Murphy, Erin; Souweidane, Mark; Fouladi, Maryam; Gajjar, Amar; Dhall, Girish; et al.
Abstract: BACKGROUND: The objective of stratum 2 of COG ACNS1123 was to evaluate children and young adults (3–21 years) with localized central nervous system (CNS) germinoma and investigate whether simplified pre-irradiation chemotherapy followed by response based dose-reduced whole ventricular irradiation (WVI) would maintain a high progression-free survival (PFS) while reducing long term treatment burden. METHODS: Pre-irradiation chemotherapy consisted of 4 cycles of carboplatin and etoposide every 21 days followed by response-based irradiation (XRT). Patients with a complete response (CR) to pre-XRT chemotherapy received 18Gy WVI + 12Gy boost to the tumor bed. Patients with partial response (PR) but less than 1.5 cm residual proceeded to 24Gy WVI + 12Gy boost. All patients were also enrolled on COG ALTE07C1 to prospectively evaluate and longitudinally model the cognitive, social and behavioral functioning. RESULTS: During a total accrual time of 45.5 months from 05/2012 to 06/2018, 137 eligible patients were enrolled. Median age was 14.09 years (4.95–21.46), 73% were male, and 45.26% had elevated βhCG in serum and/or cerebrospinal fluid. Twenty-nine patients (21.17%) did not have tissue biopsy. Eleven patients underwent second-look surgery; 7 had mature teratoma and 4 had non-viable tumor. Eighty-one patients (59.13%) had a CR. There were 4 relapses in patients receiving 18Gy WVI + boost, but no deaths. No unexpected treatment-related events were observed. The estimated 3-year PFS was 94.4 ±2.7% among 74 evaluable subjects. CONCLUSION: This study shows promise in XRT reduction for patients with localized CNS germinoma and CR. Long-term survival outcomes and ALTE07C1 data are being evaluated.